Input Shaping For Vibration-Free Positioning Of Flexible Manipulator Systems - Mohd Sufian, Abdul Karim (UTeM, 2009)
Input shaping is a method for reducing the residual vibration in positioning at the same times to move the systems. For controlling part, a continuous and differentiable function is introduced to define the desired motion and the input is shaped by inverse dynamic analysis. The shaped input function is derived from the specified output function so that the designer can choose the speed and shape of the motion within the limitations of the drive system. The simulation has been done to the spring-mass-damper system which is a second order system to study the application of the technique to the system. Next, the same technique is applied to a flexible manipulator system. In the proposed method the parameters that need to be defined is the position of the hub angle and displacement. Simulated responses of the position of the trolley and sway angle of the mass are presented using MATLAB. The performances of the inverse dynamic analysis are compared with the journal results. From the simulation results, satisfactory vibration reduction of a flexible manipulator system has been achieved using the proposed method.